<h3>
Answer: Choice A. (-2, 3)</h3>
==================================================
Explanation:
Let's try the point from choice A
We'll plug in x = -2 and y = 3
3y - x < 11
3(3) - (-2) < 11
9 + 2 < 11
11 < 11
That last statement is false, so choice A must be the answer. The point (x,y) = (-2,3) makes the inequality 3y - x < 11 false.
-----------------------
For the sake of completeness, I'll go over choices B and C.
First choice B. We plug in x = 4 and y = 1
3y - x < 11
3(1) - 4 < 11
3 - 4 < 11
-1 < 11
The last statement is true, which makes the first inequality true when x = 4 and y = 1. This shows choice B is a solution.
-----------------------
We'll now try choice C
Plug in x = -5 and y = -1
3y - x < 11
3(-1) - (-5) < 11
-3 + 5 < 11
2 < 11
The same situation occurs as did with choice B. We also have a solution here.